Pengaruh Produk Domestik Regional Bruto (PDRB) terhadap Penerimaan Pajak Daerah Kabupaten Gresik - Dina Puspita Sari; Anwar (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
This article aims to explain the effect of Gross Regional Domestic Product (GRDP) on local tax revenue in Gresik Regency. Local tax revenue is a major component of Local Own Revenue (PAD) which is an effective instrument in improving the quality of life of the community and encouraging sustainable development. The authors use a quantitative research approach with the method of documentary study of the APBD and BPS reports of Gresik Regency. The analysis technique used in this research is simple linear regression. The finding shows that Gross Regional Domestic Product affects local tax revenue in Gresik Regency with a variation in influence of 96.8%. The large variation of GRDP in influencing local tax revenue is expected that the Gresik Regency Regional Government can create a stable environment and strengthen productive sectors in GRDP which are the core in increasing regional fiscal capacity.